Traditional Agroforestry Systems Practiced in Lahaul (Lahaul & Spiti) and Kinnaur Districts of Himachal Pradesh - Kumari, Anita; Sehgal, R. N.; Kumar, Shailender (Indian Forester, 2008)
Traditional agroforestry systems prevalent in Lahaul area was agri-silvicultural system. Generally five agroforestry systems were identified i.e. agri-horticultural, agri-silvicultural, agrisilvi- pastoral, pastoral-silviculture and pastoral-horticultural. Whereas, in District Kinnaur most prevalent agro-forestry system was agri-horticultural. Four agroforestry models were identified i.e. agri-horticultural, agri-silvicultural, pastoral-silvicultural and pastoral-horticultural. Major tree species of the area were Salix, Poplar and Apple.